Stress-bearing Mechanism of Concrete Damaged by Delayed Ettringite Formation under Compressive Stress with Various Loading Patterns - Fujishima, Misato; Miura, Taito; Kawabata, Yuichiro (Journal of advanced concrete technology, 2023)
The involvement of expansion cracks in reducing compressive properties was experimentally evaluated. Concrete specimens deteriorated by delayed ettringite formation were subjected to three loading patterns (monotonic, stepwise cyclic and sustained loadings) and digital image correlation was performed to observe the behavior of expansion cracks during compressive loading. As a result, while significantly large plastic deformation was generated in the pre-peak, the reduction in compressive properties was hardly influenced by the loading patterns. The elastic strain, obtained from the loading hysteresis, increased linearly until a maximum load was reached. Consequently, two possible stress-bearing mechanism of concrete damaged by delayed ettringite formation under compressive stress was proposed to explain the development of elastic and plastic strains and the reduction in the compressive property.